An examination into the effects of very-low calorie diets and glucagon-like peptide-1 receptor agonists, individually or in combination, on skeletal muscle metabolism and glycaemic outcomes in individuals with type 2 diabetes living with obesity - Anyiam, Oluwaseun (2025)
Type 2 diabetes (T2D) and obesity are major issues of modern healthcare. Both are increasing in prevalence around the world and responsible for considerable expenditure in global health systems. On a patient level, individuals with both conditions suffer significantly from the consequences of associated complications, leading to increased levels of mortality and disability. Weight loss interventions are crucial for the management of both conditions, and two such interventions are very-low calorie diets (VLCD) and glucagon-like peptide-1 receptor agonists (GLP1RAs). They are both recommended for the treatment of T2D, and a role in weight management is also recognised.